Pengaruh Penggunaan Metode Teams Games Tournamet (TGT) Terhadap Motivasi Belajar Akidah Akhlak - Muhammad Rafli Maulana Ishak; Gunawan Ikhtiono; Kamalludin (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2024)
The purpose of this study is to evaluate the extent to which the use of methods (TGT) can increase the level of students' activation, assess students' level of motivation for study, examine the effect of the use of methods (TGT) on the increased student motivation. In view of the current problems, the performance of learning is less optimally executed, especially on traditional methods/mapping concepts, which the concept mapping method indicates that students tend to be disinterested, easily bored, and hard to maintain concentration during the learning process. In response to that, the tournament games are the solution for teachers. The study USES the tournament tournament method (TGT). Cycle observations ii show increased student learning motivation, particularly about sense position and revelation, from 55.55% in cycle I to 80.08% in cycle ii. In conclusion, student motivation has increased significantly on the basis of learning and observation during cycles I and ii. All the students have already met the KKM set in cycle